Análise de metodologias para o cálculo da descarga de fundo, aplicada ao Rio Doce, ES - Almeida, Livia Meneghel de (2012)
Knowledge of bedload transport is of primary importance in a number of aspects in watershed management, including fluvial geomorphology and ecology, stability of engineered structures and navigation condition. Despite the fundamental importance of bedload measurement, the amount of variables involved in the bedload transport mechanics, as well the complexity of the interactions among the physical processes, makes it difficult to establish a fully satisfactory criteria to determine the solid transport, thus there is not an accepted universal method. With recent advances, new methods have been proposed for measuring the bedload transport. Therewith, the aim of this study was to evaluate the suitability of methodologies for bedload measurement on a reach of the Doce River, ES. For this were used traditional direct sampling method, with Helley Smith’s sampler; formulas proposed by Einstein & Brown (1950), Engelund & Hansen (1967), Ackers & White (1973), Yang (1973) e Van Rijn (1984); bedform movement methods, considering velocity of bedform displacement and the difference between bed surfaces; and bedload velocity using an ADCP. Results indicated an unstable flow, with a bed composed primarily of fine and medium-sized sand, and bedforms in transition. Bedload values obtained by different methods showed variation of different orders of magnitude, and the highest estimates were provided by the equation of Yang (1973). The application of the bedform movement methods has been complicated by the bed condition at the site. However, the bedload measured from the velocity of bedform displacement has been quite consistent with the hydraulic conditions. The equations of Engelund & Hansen (1967) and Van Rijn (1984), and the bedload velocity method showed excellent performance, and the latter being a very promising alternative for the measurement of the bedload. To confirm the suitability of these methods in the Doce river (ES) is suggested to be carried out more measurements, in a uniform stretch, primarily using the bedload velocity and the bedform displacement methods.